The Influence of Promotion Mix and Interest Rates on Customer Interest at the Mega Auto Finance Office in Mamuju Regency - Ekaputra, Muh Irsan; Ramli, Ramli; Fajriani, Fajriani (Journal of Asian Multicultural Research for Economy and Management Study, 2023)
This research aims to find ways to implement the promotional approach carried out through PT. Mega Auto Finance Mamuju Branch to increase its profit per unit. This research uses a mix method. Researchers took a sample size of 30 people from consumers who had made transactions at PT Mega Auto Finance, Mamuju Regency. The sampling technique uses incidental sampling. Data collection techniques use observation. The results of the research show that the variables consisting of promotion auto finance in Mamuju Regency.